Ship Operation Safety: Study of Human Factors, Fatigue, and Safety Culture - Honny Fiva Akira Sembiring (Greenation Publisher, 2026)
Ship Operational Safety: Human Factors, Fatigue, and Safety Culture is a literature review article. The objective of this article is to formulate hypotheses regarding the relationships between variables to be used in future research. The study draws upon resources from online libraries, Google Scholar, Mendeley, and other academic online platforms. The research methodology employs a library research approach, utilizing e-books and open-access e-journals. The findings of this article address: 1) the influence of Human Factors on Ship Operational Safety; 2) the influence of Fatigue on Ship Operational Safety; and 3) the influence of Safety Culture on Ship Operational Safety. Keywords: Human Factors, Fatigue, Safety Culture, and Ship Operational Safety